2018
DOI: 10.14512/gaia.27.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Staatliche Eingriffe in die Lebensmittelwahl: Welche klimapolitischen Instrumente unterstützt die Bevölkerung?

Abstract: Staatliche Eingriffe in den Lebensmittelkonsum der Deutschen sind im europäischen Vergleich eher selten. Politiker(innen) empfinden wohl Lenkungssteuern- oder Werbeverbote als unpopulär. Konkrete Maßnahmen zum Klimaschutz, etwa eine Klimasteuer auf importierte Flugwaren, stoßen jedoch auf breite Zustimmung und könnten durchaus zu Klimazielen beitragen.In view of climate change, policy approaches addressing the consumption side of nutrition are becoming increasingly relevant to lowering greenhouse gas (GHG) em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Other studies assume a rather low direct effect of information on purchasing behavior (e.g., [72]). In many cases, environmental labels are not properly understood [62] (pp.…”
Section: Support At the Moment Of Decision And Activating Influencing...mentioning
confidence: 99%
“…Other studies assume a rather low direct effect of information on purchasing behavior (e.g., [72]). In many cases, environmental labels are not properly understood [62] (pp.…”
Section: Support At the Moment Of Decision And Activating Influencing...mentioning
confidence: 99%
“…Acceptance studies in the food sector have shown that taxes are strongly perceived as governmental patronization and as the illegal profits of the state, often disregarding the protective function that governmental prohibitions bring about [30]. In this context, political trust has been identified to be a strong predictor of CO 2 pricing acceptance [31][32][33].…”
Section: Public Perception and The Acceptance Of Alternative Arrangem...mentioning
confidence: 99%
“…There are several limiting policy instruments aiming at changing individual's behaviour in a politically intended direction (c.f. Garnett, 2014, Table 2; Lemken et al, 2018;Green and Gambhir, 2019, for a review of available policy instruments): regulation and legislation; fiscal measures (taxes and subsidies); nudging; social marketing. Similarly, there are also several compensatory policy instruments motivating individuals to accept the desired behavioural change: education; financial incentives; unconditioned financial compensations (negative tax).…”
Section: How Does the Proposal Compare With Other Policy Packages?mentioning
confidence: 99%
“…5 c.f. Bicket and Vanner (2016); Carattini et al (2018); Lemken et al (2018) for reviews of the research field. 6 In economic theory, the opportunity cost of a good is defined as the foregone benefit caused by choosing the good over its alternatives (taking money spent or kept into account).…”
mentioning
confidence: 99%